NON-DESTRUCTIVE INVESTIGATION OF PAINTINGS ON DIFFERENT SUBSTRATES. METHODOLOGY, ACHIEVEMENTS AND LIMITATIONS. - Kaminari, Agathi; Banou, Penelope; Moutsatsou, Anna; Alexopoulou, Athena (Design/Arts/Culture, 2022)
Today, non-destructive testing includes diagnostic methods that provide significant information for art historians, conservators and researchers. The quick in situ application, the absence of expensive consumables, the inspection of entire surfaces and the ability for mapping make these methods attractive to users. Additionally, they provide the advantage of examining large areas of work of art, supporting a multidisciplinary approach, documentation, analysis and protection of visual arts’ works. The case studies presented here involve the application of methodology on paintings on wood, canvas and paper substrate, while the constraints and particular requirements that different structures and special conditions dictate are discussed. Through these case studies the authors intend to highlight that the application of modern non-destructive methods offer many possibilities to the end user, making feasible the revelation of the painting technique, the characterization of the materials and supporting the decision making for conservation.